Functional characteristics of patients with SARS-CoV-2 pneumonia at 30 days post-infection. Issue 2 (6th August 2020) - Frija-Masson, Justine; Debray, Marie-Pierre; Gilbert, Marie; Lescure, François-Xavier; Travert, Florence; Borie, Raphaël; Khalil, Antoine; Crestani, Bruno; d'Ortho, Marie-Pia; Bancal, Catherine
We read with great interest the series of cases reported by Mo et al . [1], describing pulmonary function after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in hospitalised patients. The authors describe a significant correlation between diffusing capacity of the lung for carbon monoxide ( D LCO ) and clinically defined pneumonia severity. More than half of patients with COVID-19 pneumonia exhibit abnormal lung function 30 days after symptom onset, without clear relationship with pneumonia extent on chest CT. This pleads for systematic and long-term follow-up of patients with COVID-19. https://bit.ly/2TFMPqE